A Comparative Study Of Alternative Road Routes Based On Utility Scoring - Yudi Sekaryadi (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2026)
This study aims to determine an alternative road alignment from Cianjur to Sindangbarang in Cianjur Regency, West Java, Indonesia, functioning as a primary collector road. The method used is Multi-Criteria Analysis (MCA), which involves selecting criteria, assigning weights, calculating utility values, and identifying the best alternative. Six criteria were used: road network hierarchy integration, spatial planning integration, economic and financial aspects, social impact, environmental impact, and physical and technical aspects. The analysis results show that Alternative 4 is the most optimal route, with the highest score (32.51) and the shortest length (119.40 km) compared to the three other alternatives and the existing 150 km route. This alignment excels in road network integration and accessibility to residential, agricultural, and plantation areas, while also offering the lowest construction cost. It has minimal social and environmental impact, affecting the fewest households and causing the least disturbance during construction. The route also crosses areas with low landslide risk and high soil bearing capacity (CBR), making it technically and physically superior. The development of this road is expected to promote economic equity in South Cianjur, increasing agricultural and plantation product value and improving the income of local communities who primarily depend on farming and plantation activities.